2022
DOI: 10.1186/s43042-022-00261-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of multiplex PCR in diagnosis of childhood acute viral diarrhoea caused by rotavirus, norovirus, astrovirus and adenovirus in Upper Egypt

Abstract: Background Diarrhoea is still a major public health issue in developing countries, and it is one of the leading causes of morbidity and mortality in children. We aimed to assess the use of a multiplex reverse transcription polymerase chain reaction (RT-PCR) assay for the detection of five viruses, including rotavirus, norovirus (genogroups 1 and 2), astrovirus, and adenovirus, responsible for gastroenteritis in children under 5 years old in primary care centres in Upper Egypt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(45 reference statements)
0
2
1
Order By: Relevance
“…This is contrary to the study performed in Turkey, Italy, and the United States that found that winter is the peak season, 28,37,38 which may be linked to the temperate temperature, but rotavirus circulates throughout the year in poor countries with subtropical or tropical climates 36,38 . In agreement with our study, other study groups from Egypt and Cyprus stated that the peak season was summer 32,34 . Also, other reports from Lanzhou, Brazil, and Australia provide evidence that HAdV infection has no consistent seasonal pattern in temperate regions 39–42 …”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This is contrary to the study performed in Turkey, Italy, and the United States that found that winter is the peak season, 28,37,38 which may be linked to the temperate temperature, but rotavirus circulates throughout the year in poor countries with subtropical or tropical climates 36,38 . In agreement with our study, other study groups from Egypt and Cyprus stated that the peak season was summer 32,34 . Also, other reports from Lanzhou, Brazil, and Australia provide evidence that HAdV infection has no consistent seasonal pattern in temperate regions 39–42 …”
Section: Discussioncontrasting
confidence: 59%
“…Other studies found lower rates of rotavirus and HAdV infection than our findings as Allayeh et al, 29 who studied the detection and genotyping of rotavirus, enteric HAdV, and astrovirus in Egyptian hospitalized children below 5 years old found that the overall detection rate of rotavirus, HAdV, and coinfection was 31%, 6.7%, and 0.8%, respectively. Also, Tekin 30 found the viral antigen positive in 170/941 (18.1%) of stool samples where rotavirus and HAdV accounted for 16.7% and 1% of the variables, respectively and 0.4% coinfections; Bayraktar et al 31 stated that viral antigen positivity was detected in a total of 348/1068 of stool specimens, the rotavirus and HAdV was reported to be 23.7% and 1.5%, respectively; also, Othman et al 32 examined 50 stool samples of children with acute gastroenteritis in Egypt, 24% were infected with rotavirus and 6% were infected with HAdV.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation